Dry Eye Prevalence Among Video Display Terminals Users: A Cross-Sectional Study on Udayana University Faculty of Medicine Students - Brian, Nicholas; Triningrat, Anak Agung Mas Putrawati; Juliari, I Gusti Ayu Made (E-Jurnal Medika Udayana; Vol 11 No 8 (2022): E-Jurnal Medika Udayana, 2022)
Gadgets with Video Display Terminals (VDT) are being used daily by students all over the world. One of the effects that may arise from VDT gadgets usage for a long duration of time is Dry Eye Syndrome (DES). Dry Eye Syndrome itself can cause discomfort and may hinder productivity. OSDI is one of the few diagnosis methods for DES which uses several sets of questions in the form of questionnaire (discomfort symptoms, visual acuity, and environmental factors). The purpose of this study is to observe DES prevalence and VDT gadgets usage behaviour among students of Udayana University, Faculty of Medicine. This study is a cross-sectional descriptive study. Research data is obtained from OSDI questionnaire that was made using online form and filled through the period of July to September 2020. The data was then processed using computer software. Sample amount that is being included in this study is 228 people. The prevalence of DES among Udayana University Faculty of Medicine students is 62,3% (142 people). DES prevalence by gender is 61,6% in male students and 62,7% in female students. Usage behaviour of VDT gadgets varies by duration per day; below two hours of usage (2 sample), two to four hours of usage (21 sample), four to six hours of usage (93 sample), and above six hours of usage (112 sample) with above six hours having the average of 9,9±2,4 hours. The most common gadget that is being used among the sample is smartphone (70,6%), and the main purpose of gadget usage is for doing study assignments (36,8%). The results of this study are useful for increasing information about prevalence data of DES among students. Further research is needed to conclude a more in-depth relationship between VDT gadgets usage and DES occurrence. Keywords: Dry Eye Synrome, Video Display Terminal, OSDI.